Cultural-Psychological Models Of Experiencing Of The Person's Encounter With An Artwork - Ermolaeva, M.V.; Lubovsky, D. (Konsulʹtativnai͡a︡ psikhologii͡a︡ i psikhoterapii͡a, 2017)
Considering the perception of artworks as a higher mental function, we analyze the psychological mechanisms of the impact the mystery included by the author into the artwork has on the reader or viewer. It should be noted that the basis of any artwork’s mystery is a contradiction, which prompts the reader or viewer to solve it by retaining opposing experiences caused by the artwork. By the example of the great works of litera- ture and art, we show how a contradiction takes the viewer beyond everyday experience with the help of the metamorphosis, which turns different ideas into their opposites. The development of the reader’s or viewer’s tolerance for uncertainty or ambivalence of artworks creates opportunities for different ways of meaning generation (extension of the array of meanings, ascending the vertical of meanings, spiritual renewal through deep self-discovery). We discuss psychotechnical means of facilitating meaning generation. Рассматривая восприятие художественных произведений как высшую психическую функцию, авторы анализируют психологические механизмы воздействия на зрителя или читателя тайны, заложенной автором в художественное произведение. Отмечено, что основа тайны любого произведения искусства и литературы представляет собой противоречие, которое для зрителя или читателя создает ситуацию, требующую разрешения за счет удержания противоположностей в его переживании, вызванном произведением. На примерах великих произведений литературы и искусства авторы показывают, как противоречие выводит зрителя за рамки повседневного опыта благодаря метаморфозам, в которых различные начала превращаются в свою противоположность. Развитие толерантности читателя или зрителя к неопределенности-амбивалентности художественного произведения создает возможности для различных путей смыслопорождения (расширения смыслового горизонта, движения по смысловой вертикали, духовного обновления за счет глубокого самопознания). Авторы обсуждают психотехнические средства фасилитации смыслопорождения.